INDOBIOSYS – DNA BARCODING AS A TOOL FOR THE RAPID ASSESSMENT OF HYPERDIVERSE INSECT TAXA IN INDONESIA: A STATUS REPORT - Bruno Cancian de Araujo; Stefan Schmidt; Thomas von Rintelen; Hari Sutrisno; Kristina von Rintelen; Rosichon Ubaidillah; Christoph Häuser; Djunijanti Peggie; Raden Pramesa Narakusumo; Michael Balke (BRIN Publishing (Penerbit BRIN), 2017)
A status report with preliminary results for the IndoBioSys project is presented and the impact of the project results for our knowledge of the Indonesian fauna is discussed. Using the REST API available on the Barcode of Life Data System we recover 21,153 public records (3,390 BINs) from Indonesia and compare against the 21,813 records (3,580 BINs) generated by the IndoBioSys project. From all IndoBioSys BINs, 3,366 (94%) are new to Indonesia. IndoBioSys is responsible for a BIN increase of 36.5% in Lepidoptera, 62.6% in Trichoptera, 986% in Coleoptera, and 1,086% in Hymenoptera. After two years of the IndoBioSys project, the Museum Zoologicum Bogoriense became the depository institution of 51.9% of Lepidoptera records, 95.8% of Coleoptera records, 97.6% of Hymenoptera records and 59.4% of Trichoptera records for Indonesia available on Barcode of Life Data System (BOLD). Now, with 55% of all Indonesian records available on BOLD, it is the most important depository for records of Indonesian genetic biodiversity, housing more than 23,000 new voucher specimens in their collections. Before IndoBioSys, the Museum Zoologicum Bogoriense was responsible for only 9% of all records available in the Barcode of Life Data System for Indonesia, showing the importance of those pipelines in empowering the local institutions in becoming the reference depository of the local fauna.